2020
DOI: 10.3354/dao03538
|View full text |Cite
|
Sign up to set email alerts
|

Association between ALFPm3 single nucleotide polymorphism and white spot syndrome virus resistance in black tiger shrimp Penaeus monodon

Abstract: Here single nucleotide polymorphisms (SNPs) were associated with white spot syndrome virus (WSSV) resistance in black tiger shrimp Penaeus monodon. SNPs were identified by single-strand conformation polymorphism (SSCP) screening and DNA sequencing of shrimp sampled from 3 families (100 shrimp per family) challenged with WSSV. Shrimp that died over the 14 d challenge trial were designated susceptible, with those remaining alive on Day 14 designated resistant. To compare SNPs, 10 samples from the susceptible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The band lines on the DNA marker holes will be visible and glow at every 100 bp size. DNA markers that function to verify the size of the genotype of the virus will fluoresce well indicates that the PCR test process is running well without any contamination [7]. The second hole is positive control of WSSV virus that appears at a length of 941 bp.…”
Section: Resultsmentioning
confidence: 99%
“…The band lines on the DNA marker holes will be visible and glow at every 100 bp size. DNA markers that function to verify the size of the genotype of the virus will fluoresce well indicates that the PCR test process is running well without any contamination [7]. The second hole is positive control of WSSV virus that appears at a length of 941 bp.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of disease resistance, such genetic variation resulting in stock improvement can be slight. For example, a single nucleotide polymorphism (SNP) (g.1186A > G) in the anti‐lipopolysaccharide factor 3 (ALFPm3) gene of P. monodon has been associated with higher rates of survival during WSSV challenge 92 . This SNP was found to be variably present among three independent sources of farmed shrimp within the same province in Thailand, highlighting the importance of specific reporting of shrimp source for contextualisation of PCE findings.…”
Section: Essential Components Of Viral Pathogen Challenge Experiments...mentioning
confidence: 99%
“…As example of the appli- Molecular markers based on single nucleotide polymorphisms (SNPs) have been recently implemented for selecting for growth performance, 113,114 resistance to V. parahaemolyticus in P. vannamei, 111,115 parvovirus in P. mergulensis 116 or even different stressors such as nitrite concentration. 117 Recently, Pooljun et al 118 have found an association between a SNP in the anti-lipopolysaccharide factor 3 (ALF3) and resistance to WSSV in P. monodon. These results open a new way to fight against the different diseases that threaten the industry with massive pathogenic outbreaks.…”
Section: Future Per S Pec Tive S and Con Clus Ionsmentioning
confidence: 99%
“…mergulensis 116 or even different stressors such as nitrite concentration 117 . Recently, Pooljun et al 118 have found an association between a SNP in the anti‐lipopolysaccharide factor 3 (ALF3) and resistance to WSSV in P . monodon .…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%